The freedman in the Roman world - Mouritsen, Henrik (Cambridge University Press, 2011)
"Freedmen occupied a place in Roman society between slaves on the one hand and full citizens on the other. Playing an extremely important role in the economic life of the Roman world, they were also a key instrument for replenishing and even increasing the size of the citizen body; but their position between slave and citizen was of course not unproblematic. Henrik Mouritsen presents an original synthesis of Roman manumission, for the first time covering both Republic and Empire in a single volume. While providing up-to-date discussions of most significant aspects of the phenomenon, the book also offers a new understanding of the practice itself, its role in the organisation of slave labour and the Roman economy, as well as the deep-seated ideological concerns to which it gave rise. It locates the freedman in a broader social and economic context, explaining the remarkable popularity of manumission in the Roman world"--